Transforming Disguised Unemployment through Youth Entrepreneurship: The Role of Islamic Banking among Senior and Vocational High School Graduates in Rural Areas - Hasibuan, Amanda Mutiara; Nawawi, Zuhrinal M.; Nurbaiti (Universitas Muhammadiyah Pontianak, 2026)
This study examines disguised unemployment among senior and vocational high school graduates in Mompang Village and the role of Islamic banking in promoting youth entrepreneurship. Using a qualitative case study, data was collected through observation and interviews with 13 informants. The findings show that graduates are often trapped in low-productivity informal work marked by educational mismatch, unstable income, and limited career prospects. Entrepreneurship offers a pathway to economic independence but is hindered by limited capital, skills, and institutional support. Islamic financing has transformative potential when integrated with mentoring, financial literacy, and business development. Keywords: Disguised Unemployment; Youth Entrepreneurship; Islamic Financial Inclusion; Rural Labor Transformation; Vocational School Graduates